ANALISIS PENGARUH KUALITAS PELAYANAN, FASILITAS, HARGA, KEPERCAYAAN & PRODUT KNOWLEDGE TERHADAP KEPUASAN PASIEN (STUDI KASUS DI KLINIK RUMAH SEHAT HERBAL CENTER) - Urfa, Nurul Fathiyah; Pragiwani, Meita (LPPM Politeknik Pajajaran ICB Bandung, 2024)
This study aims to test the effect of quality of service, facilities, pricing, trust, and product knowledge on patient satisfaction at the Sehat Herbal Center Clinic (RSHC). The research uses associative-causal (causality) quantitative approach. The analytical technique used in this study is Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The population for this study consists of all patients visiting the Sehat Herbal Center Clinic (RSHC). The sample was determined using a Nonprobability Sampling method, with a sample size of 100 patient. The data used in this study is primer data. Data collection was conducted using an online questionnaire via Google Forms. Hypothesis testing was performed using path coefficient tests, T-Statistics, and P-Values. The results of the study indicate that service quality does not affect patient satisfaction, facilities do affect patient satisfaction, pricing does not affect patient satisfaction, trust does affect patient satisfaction, and product knowledge also affects patient satisfaction